2016
DOI: 10.1515/cclm-2015-0243
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of several biomarkers in the management of septic patients: C-reactive protein, procalcitonin, presepsin and mid-regional pro-adrenomedullin

Abstract: PCT, MR-proADM and presepsin are complementary markers that could be of great help in the management of septic patients when they are measured in the first 24 h after ICU admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 19 publications
6
40
0
3
Order By: Relevance
“…Procalcitonin (PCT), which is a novel marker of inflammation and infection, has been widely investigated for its prognostic value in septic patients. Although studies have produced conflicting results [30][31][32][33][34][35][36], Tasdelen Fisgin et al [30] and Hensler et al [32] demonstrated that neopterin was a better prognostic factor than PCT in patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Procalcitonin (PCT), which is a novel marker of inflammation and infection, has been widely investigated for its prognostic value in septic patients. Although studies have produced conflicting results [30][31][32][33][34][35][36], Tasdelen Fisgin et al [30] and Hensler et al [32] demonstrated that neopterin was a better prognostic factor than PCT in patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Enguix-Armada et al [48] in a 388-patient cohort assessed whether the combination of CRP, PCT, presepsin and MR-proADM measured in the first 24 hours after ICU admission allows better management of septic patients. In their results PCT showed the highest AUC (0.989) as compared with the rest of the biomarkers (P < 0.01).…”
Section: Role Of Mid-regional Fragment Of Pro-adrenomedullin In Sepsismentioning
confidence: 99%
“…is well established that presepsin is a useful marker in the diagnosis of sepsis [1,[6][7][8][9]. Studies on comparison of presepsin with conventional biomarkers (C-reactive protein [CRP], procalcitonin [PCT], etc.)…”
Section: Structure and Mechanism Of Presepsinmentioning
confidence: 99%
“…Godnic et al [30] investigated expression of CD64 on neutrophils Brought to you by | Stockholms Universitet Authenticated Download Date | 10/5/15 9:09 AM [19] 388 patients in ICU Has the highest AUC Enables the difference between Grampositive and Gram-negative bacteria Superior when combined with CRP and MR-proADM [6] 47 patients with SIRS, septic shock and sepsis Determines possible infection Predicts SIRS severity and distinguishes between sepsis and severe sepsis or septic shock Determines possible infection [30] 39 patients of nephrolithiasis who were diagnosed as SIRS Higher diagnostic value [28] Reports of 4 cases with renal dysfunction High, even infection does not exist [26] 19 newborns with LOS Useful for the diagnosis of LOS and monitoring the response to treatment [20] 191 patients with SIRS Superior in diagnosis of DIC [23] Review Better sensitivity and specificity in the diagnosis of sepsis [1] 116 patients with sepsis or septic shock Better diagnostic and prognostic value [29] Comparison of infection and non-infection groups Better in diagnosis and treatment of bacterial sepsis [10] Review Superior in diagnosing sepsis, assessing the severity of the disease and providing a prognostic evaluation of patient outcome [16] 21 patients in ICU with sepsis Returns to normal levels during the transient remission phase Remains high during the transient remission phase.…”
Section: Presepsin and Intensive Carementioning
confidence: 99%